2010
DOI: 10.1111/j.1748-1716.2009.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic preconditioning is related to decreasing levels of extracellular adenosine that may be metabolically useful in the at‐risk myocardium: an experimental study in the pig

Abstract: Preconditioning up-regulates a new metabolic pathway (starting with 5'-nucleotidase and ending up with lactate) resulting in ATP formation in the micromolar range on top of another effect terminating in a useful shift in the AK equilibrium reaction in favour of ATP generation in the millimolar range. Although the up-regulation of the purine nucleoside phosphorylase pathway is clearly demonstrated, its biological relevance remains to be proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
(60 reference statements)
2
10
0
1
Order By: Relevance
“…These exosomes also carry CD73 (5′-nucleotidase) that can produce extracellular adenosine, a well-known mediator of protection in ischemic preconditioning. [120][121][122] Finally, the inflammatory reaction to ischemia was shown to be reduced. 123 It is still not known which exosomal factors are most important for the effects described above, but this body of results so far supports the interpretation that certain growth factors and cytokines, such as basic fibroblast growth factor, tumor necrosis factor-α, TGF-β, epidermal growth factor, heat shock proteins (HSP20, 60, and 70), and miRs known to be carried by exosomes, are, at least in part, responsible for the response.…”
mentioning
confidence: 95%
“…These exosomes also carry CD73 (5′-nucleotidase) that can produce extracellular adenosine, a well-known mediator of protection in ischemic preconditioning. [120][121][122] Finally, the inflammatory reaction to ischemia was shown to be reduced. 123 It is still not known which exosomal factors are most important for the effects described above, but this body of results so far supports the interpretation that certain growth factors and cytokines, such as basic fibroblast growth factor, tumor necrosis factor-α, TGF-β, epidermal growth factor, heat shock proteins (HSP20, 60, and 70), and miRs known to be carried by exosomes, are, at least in part, responsible for the response.…”
mentioning
confidence: 95%
“…Microdialysis sampling can be performed in organs which move, and this technique has been used to study metabolic aspects of the beating heart (Kavianipour et al. , 2003; Waldenström et al. , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Microdialysis facilitates serial biochemical sampling through a probe which lies within the substance of an organ. Serial sample collection is based on passive diffusion through a semi-permeable membrane placed at the end of the sampling probe (Ungerstedt, 1991;Chaurasia, 1999;Stahl et al, 2002;Kavianipour et al, 2003;Waldenström et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In heart ischemia, IPC has been shown to increase the lactate levels in a stepwise fashion correlating to lower lactate levels during the later, more severe ischemic insult [34]. It has been suggested that lactate released during IPC may inhibit the breakdown of ATP during later, more severe ischemia, as well as induce ATP formation from adenosine yielding [35].…”
Section: Discussionmentioning
confidence: 99%